Women in the public discourse in the period of the Tuvan People’s Republic (A historical and sociological analysis based on materials of the periodical press) - Natsak, Organa D. (The New Research of Tuva, 2023)
The article presents a historical and sociological analysis of the development of a modern Tuvan woman. It is based on the materials of Tuvan magazines and newspapers published in the years of the Tuvan People’s Republic (TPR). Through the analysis of public discourse, the author has described the content of the policy towards women, as well as ideologically marked images of females which were correlated with the sociocultural and political context of the period under consideration. The article showcases the methods and features of the legal socialization of women.The author characterizes the practices of representation of women in Tuvan magazines and newspapers. Through newspaper narratives, the content of the social design of the “new Tuvan woman” has been revealed. The work presents the results of an interpretive analysis of slogans that were addressed to women. These mottos demonstrate challenges and tasks that were being handled at the state level as well as the target model that they were seeking. The author discloses the principles of the work of aratkors (people’s correspondents) and the influence of their letters on women's careers in the conditions of the then emerging new political culture, which is characterized by features similar to those of contemporary “culture of cancellation”, the spread of the fight against “enemies of the people” and the penetration of the language of violence into political communication.It is concluded that Tuvan magazines and newspapers of the TPR period contributed to the female role revolution.
Keywords: Tuvans; Tuvan People’s Republic; periodical press; history of Tuva; women’s issue; legal socialization; social design; modernization; class struggle; political culture; culture of anonymity; newspaper narrative